2021
DOI: 10.1016/j.adro.2020.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Radiation Therapy for Metastatic, Persistent, or Recurrent Epithelial Ovarian Cancer: Efficacy in the Era of Modern Technology and Targeted Agents

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Even without serious CNS toxicity in acute or early-delayed phase, delayed significant CNS toxicity of this fractionated radiotherapy still could be a concern (30). Recently, Butala et al reported that cumulative biologically effective doses >39 Gy were associated with improved clinical response in CNS lesions without obvious toxicities, but there was a lack of information on tumor sizes in this study (31). GKS has overcome several of these limitations in a fundamental way.…”
Section: Discussionmentioning
confidence: 71%
“…Even without serious CNS toxicity in acute or early-delayed phase, delayed significant CNS toxicity of this fractionated radiotherapy still could be a concern (30). Recently, Butala et al reported that cumulative biologically effective doses >39 Gy were associated with improved clinical response in CNS lesions without obvious toxicities, but there was a lack of information on tumor sizes in this study (31). GKS has overcome several of these limitations in a fundamental way.…”
Section: Discussionmentioning
confidence: 71%
“…Generally ovarian cancer carries a high risk of late presentation and poor outcomes, but this risk is worse in Africa where diagnostic and treatment capacity is limited 9 10. In modern practice, radiotherapy is typically not employed in the management of ovarian cancer, except for localized palliative treatment 11…”
Section: Role and Place Of Radiotherapy For Gynecological Malignancie...mentioning
confidence: 99%
“…9 10 In modern practice, radiotherapy is typically not employed in the management of ovarian cancer, except for localized palliative treatment. 11…”
Section: Role and Place Of Radiotherapy For Gynecological Malignancie...mentioning
confidence: 99%
“…In vulvar cancer, the target includes the intact primary disease or the post-surgical bed with or without treatment to the pelvis or inguinal lymph nodes. Radiotherapy for ovarian cancer is limited in routine use, but can be used effectively in palliation 5. Treatment at these regions may expose significant volumes of normal tissues to radiation-related toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Radiotherapy for ovarian cancer is limited in routine use, but can be used effectively in palliation. 5 Treatment at these regions may expose significant volumes of normal tissues to radiation-related toxicity. Toxicities include acute and late damage to the bowel, rectum, bladder, bone, and bone marrow.…”
Section: Introductionmentioning
confidence: 99%